PENGARUH KOMITMEN ORGANISASIONAL, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PROVINSI RIAU - Viska Audra Dinda; Machasin Machasin; Musfar Firli T (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted at the Riau Provincial Education Office. The purpose of this study was to analyze the influence of Organizational Commitment, Competence and Work Discipline on Performance either partially or collectively on Riau Province Education Office Employees. The population in this study were all employees of the Riau Province Education Office, while the sample in this study were 143 representatives of the Riau Province Education Office employees who had been randomized. The data analysis technique used in this study is multiple linear regression analysis. The results of this study conclude (1) there is a significant and positive direct influence between Organizational Commitment on the performance of the Riau Provincial Education Office Employees, (2) there is a significant and positive direct influence between Competence and Performance of the Riau Provincial Education Office Staff, (3) There is a significant direct influence between Work Discipline on Performance in Riau Province Education Office Employees, and (4) there is a significant influence between Organizational Commitment, Competence and Work Discipline together on the Performance of Riau Provincial Education Service Employees, with the magnitude of the influence is 43.8%, while the remaining 56.2% is influenced by other variables.Keywords: Organizational Commitment, Competence, Work Discipline and Performance